Hydrotherapy resources used in patients with fibromyalgia: A review (Research, Society and Development, 2022)
Fibromyalgia is a rheumatologic pathology that has a predominance in female patients, leading to various impairments in their daily activities. This disease does not have a fully clarified reason, but it is known that it has a great relationship with the nervous system. In order to have a fibromyalgia diagnosis, it is necessary that the patient has at least three months of consecutive pain on both sides of the body. In this way, physiotherapy comes with the aim of alleviating deficits and relieving patients' pain, bringing a better quality of life. And hydrotherapy's method is to provide the release of neurotransmitters that improve the patient's conditioning since it is a treatment done inside heated pools causing sensations of immediate relief and global relaxation of the body. Therefore, it is necessary to study the improvement of fibromyalgia in the context of hydrotherapy, as this method is of paramount importance in the treatment of the individual so that the methods that will be used within the aquatic environment with the patient are improved.